Psychological Well-Being Among Young People Living with HIV: Role of Social Support, Self-Esteem and Socio-Demographic Variables - Muwonge, Charles Magoba; Kembabazi, Annet; Nakalema, Gladys; Ekatushabe, Margaret; Kwarikunda, Diana; Kibedi, Henry; Ssenyonga, Joseph (Research Perspectives, 2022)
The focus of the present study was two-fold: (a) to examine the relations between demographic characteristics and the psychological well-being of Young People Living with HIV (YPLWH) and (b) to assess the extent to which self-esteem mediated the relationship between social support and psychological well-being of YPLWH. The sample consisted of 181 YPLWH selected from four Primary Health Care clinics in South-Western Uganda who responded to anonymous self-administered questionnaires. Data were analyzed using t-tests, ANOVA, and path analysis. We noted that females had significantly higher purpose in life scores than males (p < .05). General family support exerted direct effects on purpose in life (β ¼ .40, p < .001) and positive relations (β ¼ .15, p < .001). The effects of general family support on personal growth were mediated by self-esteem (β ¼ .14, p < .001). Conversely, the total contributions of support from friends on personal growth and positive relations were mostly direct rather than being mediated by self-esteem. The study highlights a need to enhance the social support networks as a way of enhancing self-esteem and ensuring psychological well-being among YPLWH in Uganda.
Keywords: Psychological well-being; Self-esteem; Social support; Socio demographic variables; Young people living with HIV